Otto Warburg: The journey towards the seminal discovery of tumor cell bioenergetic reprogramming - Urbano, Ana M. (Biochimica et biophysica acta. Molecular basis of disease, 2021)
Metabolic reprogramming is now regarded as a hallmark of cancer. This phenomenon was first observed at the level of cellular energetics, in the form of very high rates of lactic acid fermentation, not only in anoxia, but also in the presence of oxygen levels that do not compromise respiration. This intriguing tumor phenotype, characterized by a very low energy yield, was unveiled, in the early 1920s, by Otto Warburg, one of the greatest biochemists of all time. This manuscript outlines aspects of Warburg's personal and research life that, in retrospect, might be viewed as a preparation for his successful approach to the cancer problem. It also discusses the experiments that led to the discovery and briefly presents Warburg's theory for the origin of tumors. Finally, it concludes with considerations regarding the novel avenues that this monumental and still intriguing discovery opened in terms of diagnosis and treatment of cancer. •Otto Warburg is one of the greatest biochemists of all time.•Otto Warburg unveiled the first tumor-specific metabolic phenotype.•Tumor cells rely heavily on fermentation for the generation of metabolic.•The discovery of the Warburg effect was not accidental.•Otto Warburg developed biochemical manometry and the tissue slice technique.